Peer teaching as a methodology to teach grammar: A case study / Badli Esham Ahmad - Ahmad, Badli Esham (Universiti Teknologi MARA Cawangan Pahang, 2002)
The study aims at investigating the possibilities of using peer teaching in teaching grammar. The study was conducted on the Pre-Diploma students and the findings suggest that peer teaching does help to improve students' level of understanding of English Language.